Use of digital panoramic radiography to detect cervical calcifications in obese individuals - Abreu, Saulo Gonçalves de; Simoes, Natália Myrrha; Zanini, Ana Paula; Girundi, Marcelo Gomes; Silva, Amaro Ilidio Vespasiano; Manzi, Flavio Ricardo (Journal of Oral Diagnosis, 2017)
Introduction: Cardiovascular diseases and stroke in particular are the leading causes of death worldwide. The most common reason for this interruption is a buildup of fatty deposits on the inner walls of blood vessels; upon calcification, these deposits are termed atheromas. Objective: The aim of this study was to identify calcified atherosclerotic plaque- -like soft tissue calcifications in obese subjects using panoramic radiography. Materials and Methods: Sixty-three obese patients undergoing digital panoramic radiography in a radiology clinic in Belo Horizonte, Brazil, were selected and diagnosed with grade II obesity with comorbidities and grade III obesity according to the World Health Organiza- tion (WHO) body mass index (BMI) score table. The radiographs were examined by two trained oral and maxillofacial radiologists, and their evaluations were analyzed using the kappa test. Statistical analysis was performed using the X2 test, and the odds ratio was determined with a 95% confidence interval. A 5% significance level was used. Results: The weight and BMI (p < 0.01) differed significantly between individuals in the grade II with comorbidities and grade III groups, but no difference was observed for age and height. Of 63 radiographs, 45 (71.42%) showed calcifications in the cervical region, with no statistically significant difference between the grade II and grade III groups. Neither gender nor side was significantly correlated with the presence of soft tissue calcification. Conclusion: This study demonstrates the importance of panoramic radiography in iden- tifying calcified atheromatous plaques. Such images may have critical diagnostic value for the early detection of carotid artery atheromas in obese subjects and thus may contribute to an increase in the length and quality of life of such individuals.